Three-dimensional eye position signals shape both peripersonal space and arm movement activity in the medial posterior parietal cortex - Hadjidimitrakis, Kostas; Breveglieri, Rossella; Bosco, Annalisa; Fattori, Patrizia (Frontiers in Integrative Neuroscience, 2012)
Research conducted over the last decades has established that the medial part of posterior parietal cortex is crucial for controlling visually guided actions in human and non-human primates. Within this cortical sector there is area V6A, a crucial node of the parietofrontal network involved in arm movement control in both monkeys and humans. However, the encoding of action-in-depth by V6A cells had been not studied till recently. Recent neurophysiological studies show the existence in V6A neurons of signals related to the distance of targets from the eyes. These signals are integrated, often at the level of single cells, with information about the direction of gaze, thus encoding spatial location in 3D space. Moreover, 3D eye position signals seem to be further exploited at two additional levels of neural processing: a) in determining whether targets are located in the peripersonal space or not, and b) in shaping the spatial tuning of arm movement related activity towards reachable targets. These findings are in line with studies in putative homolog regions in humans and together point to a role of medial posterior parietal cortex in encoding both the vergence angle of the eyes and peripersonal space. Besides this role in spatial encoding also in depth, several findings demonstrate the involvement of this cortical sector in non-spatial processes.